Influence of Blast Furnace Slag and Fly Ash on Strength Properties of Clayey Soil: A Comparative Study - Tangri , Amanpreet; Singh, Jagseer (International Journal For Research In Mechanical & Civil Engineering, 2016)
Soil stabilization is a major problem in construction engineering and the researches are effectively using rapidly generating industrial wastes. This present experimental work describes about the stability of clayey soil with Blast furnace slag and Rice husk ash individually by using Lime. The main aim is to minimize the industrial waste generated by industry. The cost of stabilization by normally used common techniques has become costlier day by day such as cement, lime etc. So replacement of natural soils, aggregates with industrial by product is extremely desirable. This also reduces environmental hazards. In this study the unconfined compressive strength of clayey soil was studied by using Blast furnace slag and Rice husk ash. Lime was also mixed with both Blast furnace slag and Rice husk ash. In the starting of the study lime was optimized and the optimized amount of lime was found to be 4%. It was determined by performing unconfined compressive strength test and adopting the curing period of 7 days. Then this optimum amount was used for further study with Blast Furnace Slag and RHA on clayey soil for determining the unconfined compressive strength for both materials separately and using fixed amount of lime. Various percentages of Blast Furnace Slag and Rice Husk Ash were 10%, 20%, 30%, 40% and 50%. The unconfined compressive strength was found to be maximum at 10% RHA,4% lime and 86% of soil.